The MIDA Mortality Risk Score: development and external validation of a prognostic model for early and late death in degenerative mitral regurgitation. (13th August 2017) - Grigioni, Francesco; Clavel, Marie-Annick; Vanoverschelde, Jean-Louis; Tribouilloy, Christophe; Pizarro, Rodolfo; Huebner, Marianne; Avierinos, Jean-Francois; Barbieri, Andrea; Suri, Rakesh; Pasquet, Agnés; Rusinaru, Dan; Gargiulo, Gaetano D; et al.
Abstract: Aims: In degenerative mitral regurgitation (DMR), lack of mortality scores predicting death favours misperception of individual patients' risk and inappropriate decision-making. Methods and results: The Mitral Regurgitation International Database (MIDA) registries include 3666 patients (age 66 ± 14 years; 70% males; follow-up 7.8 ± 5.0 years) with pure, isolated, DMR consecutively diagnosed by echocardiography at tertiary (European/North/South-American) centres. The MIDA Score was derived from the MIDA-Flail-Registry (2472 patients with DMR and flail leaflet-Derivation Cohort) by weighting all guideline-provided prognostic markers, and externally validated in the MIDA-BNP-Registry (1194 patients with DMR and flail leaflet/prolapse-Validation Cohort). The MIDA Score ranged from 0 to 12 depending on accumulating risk factors. In predicting total mortality post-diagnosis, the MIDA Score showed excellent concordance both in Derivation Cohort ( c = 0.78) and Validation Cohort ( c = 0.81). In the whole MIDA population ( n = 3666 patients), 1-year mortality with Scores 0, 7–8, and 11–12 was 0.4, 17, and 48% under medical management and 1, 7, and 14% after surgery, respectively ( P < 0.001). Five-year survival with Scores 0, 7–8, and 11–12 was 98 ± 1, 57 ± 4, and 21 ± 10% under medical management and 99 ± 1, 82 ± 2, and 57 ± 9% after surgery ( P < 0.001). In models including all guideline-provided prognostic markers and the EuroScoreII, the MIDA Score provided incremental prognostic information ( P ≤ 0.002). Conclusion: The MIDA Score may represent an innovative tool for DMR management, being able to position a given patient within a continuous spectrum of short- and long-term mortality risk, either under medical or surgical management. This innovative prognostic indicator may provide a specific framework for future clinical trials aiming to compare new technologies for DMR treatment in homogeneous risk categories of patients.